A Mentored Pathway into the Sciences for Underrepresented Populations: A Newly Crafted Educational Modality for Women Exploring Career Opportunities in Science, Technology, Engineering, Mathematics, and Medicine - Sheindel Ifrah Goldfeiz; Miriam Knoll; Reshma Jagsi; Chana Weinstock; James W. Pennebaker; Linda Samuels; Daniel C. Edelman (Women's Health Reports, 2020)
Purpose: The barriers generally facing women wishing to pursue careers in the disciplines of science, technology, engineering, mathematics, and medicine (STEMM) in the United States have been well described. However, additional layers of cultural beliefs and needs may pose further obstructions to women in certain cultural subgroups who wish to enter STEMM. Recognition of the challenges faced by such subgroups is important and culturally sensitive educational and training approaches may be necessary. Methods: We therefore created a science mentoring and education program incorporating the specific requirements of our test group, young Orthodox Jewish women. Our goals were to facilitate their knowledge, skills, and attitudes to embark on a scientific career in biomedicine. Interventions were designed to target physical, intellectual, emotional, and spiritual areas of growth with each intervention crafted to the sensitivity of the women's cultural and religious backgrounds. Results: Over the course of 6 years, we enrolled 59 Orthodox Jewish women, ages 16?20 years. These women spent their summers as part of the larger Summer Internship Program (SIP) at the National Institutes of Health. They participated in cohort sizes ranging from 6 to 26 in dozens of multilevel experiences in the SIP over 6?10 weeks. Participants reported strengthening interest to pursue careers in health care-related fields. Other graduates committed to pursue careers in the general sciences, and other graduate studies. Conclusion: This unique educational platform shows promise for other intersectional groups approaching educational barriers to careers in STEMM.